2015
DOI: 10.1039/c5sc02528a
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the deselenization of selenocysteine into alanine and serine

Abstract: The deselenization of selenocysteine selectively removes the selenol group to give alanine under anaerobic conditions or serine under aerobic conditions (oxygen saturation).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
123
1
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(132 citation statements)
references
References 63 publications
(97 reference statements)
0
123
1
8
Order By: Relevance
“…Recently, we (and others) were excited to find that the radical quencher, sodium ascorbate, completely inhibits the undesired deselenization (or desulfurization) reaction that occurs in the presence of TCEP, a commonly used reductant in NCL reactions. 44,68 Therefore, all Sec-NCL reactions for SELM synthesis were performed in a buffer containing both TCEP and sodium ascorbate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we (and others) were excited to find that the radical quencher, sodium ascorbate, completely inhibits the undesired deselenization (or desulfurization) reaction that occurs in the presence of TCEP, a commonly used reductant in NCL reactions. 44,68 Therefore, all Sec-NCL reactions for SELM synthesis were performed in a buffer containing both TCEP and sodium ascorbate.…”
Section: Resultsmentioning
confidence: 99%
“…Under anaerobic conditions, the deselenization 34,44 of SELM(48–145) (U48Sez–A78U–A107U) using TCEP in the presence of DTT was completed in 24 h (Fig. S8†).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6a] This methodology can also be extended to ligation-deselenization at selenol-derived amino acid residues. [7] Independently, our laboratory [8] and Metanis and co-workers, [9] recently demonstrated that, in the presence of an oxidant to outcompete hydrogen atom abstraction, Sec can be transformed into serine (Ser) at the ligation junction which provides a further expansion of Sec-based ligations. While this oxidative deselenization can be performed using O2 as an oxidant, [8][9] peptide cleavage products were observed on larger peptide targets.…”
Section: Sec Followed By Deselenization (Right) or Oxidative Deselenimentioning
confidence: 99%
“…[7] Independently, our laboratory [8] and Metanis and co-workers, [9] recently demonstrated that, in the presence of an oxidant to outcompete hydrogen atom abstraction, Sec can be transformed into serine (Ser) at the ligation junction which provides a further expansion of Sec-based ligations. While this oxidative deselenization can be performed using O2 as an oxidant, [8][9] peptide cleavage products were observed on larger peptide targets. [8] For this reason, following optimization, we arrived at oxone® as an oxidant that could facilitate clean conversion of Sec to Ser in minutes in the presence of TCEP (Scheme 1B).…”
Section: Sec Followed By Deselenization (Right) or Oxidative Deselenimentioning
confidence: 99%